2015
DOI: 10.2527/jas.2014-8026
|View full text |Cite
|
Sign up to set email alerts
|

Copper bioavailability, blood parameters, and nutrient balance in mink1

Abstract: A 3 × 3 + 1 factorial experiment was conducted based on a completely randomized design to evaluate the effects of different sources of copper on plasma metabolites, nutrient digestibility, relative copper bioavailability, and retention of some minerals in male mink. Animals in the control group were fed a basal diet, which mainly consisted of corn, fish meal, meat and bone meal, and soybean oil, with no copper supplementation. Mink in the other 9 treatments were fed the basal diet supplemented with Cu from rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…The present study indicated that formulated diets were less digestible than the conventional one, which is comparable to a study carried out on another fur-bearing animal species, the fox (Gugołek et al 2010). The high EE digestibility suggests that mink can utilize fat from different sources, as shown by several researches which applied dry experimental diets on mink (Wu et al 2014(Wu et al , 2015Liu et al 2016). Significant differences were reported for CP digestibility in the present study.…”
Section: Feed Intake Dm and Nutrient Digestibilitysupporting
confidence: 82%
“…The present study indicated that formulated diets were less digestible than the conventional one, which is comparable to a study carried out on another fur-bearing animal species, the fox (Gugołek et al 2010). The high EE digestibility suggests that mink can utilize fat from different sources, as shown by several researches which applied dry experimental diets on mink (Wu et al 2014(Wu et al , 2015Liu et al 2016). Significant differences were reported for CP digestibility in the present study.…”
Section: Feed Intake Dm and Nutrient Digestibilitysupporting
confidence: 82%
“…At the end of the experiment, blood samples were taken via the toe clip from mink in the morning after overnight fasting for determining concentrations of serum Zn and serum biochemical parameters. Blood samples were centrifuged at 3,000 × g for 10 min at 4°C, and serum samples were collected and stored at −20°C until being analyzed (Wright and Spears, 2004;Wu et al, 2015c). Liver, pancreas, and the right tibia of each mink were collected at the abattoir and stored at −20°C until being analyzed.…”
Section: Experimental Procedures and Sample Collectionmentioning
confidence: 99%
“…The source of ZnPOS that consists of α-(1,4)-linked POS units was obtained from the Feed Research Institute, Chinese Academy of Agricultural Sciences, and the content of Zn in the ZnPOS was 7% by calculation. The basal diet consisted of corn, meat, fish meal and bone meal, and soybean oil, with no added Zn in the premix and was formulated to meet the Zn requirements of growing mink (Wu et al 2015b). Zn content in the control diet was 65.18 mg/kg by analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The activities of aspartate aminotransferase (AST), serum alanine transaminase (ALT), glucose (GLU), and alkaline phosphatase (ALP), and the contents of serum total protein (TP), albumin (ALB), and glutamyltransferase (GGT) were analyzed by an automatic biochemistry analyzer Hitachi 7020 (Hitachi High Technologies, Inc., Japan) with kits being supplied by the Nanjing Jiancheng Bioengineering Research Institute, China. Zn dependent enzyme activities of serum Cu-Zn superoxide dismutase (Cu-ZnSOD) were measured using commercially available assay kits purchased from the Nanjing Jiancheng Bioengineering Research Institute (Wu et al 2015b). The apparent digestibility (AD) of nutrients and energy was calculated as follows (Wu et al 2014):…”
Section: Methodsmentioning
confidence: 99%